Better methods to measure the emissions of small-scale farming: smallholder farmers and climate change: options and information - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Smallholder farmers provide up to 80 percent of the food supply in sub-Saharan Africa and Asia. Yet very little is known about either the contribution of smallholder systems to greenhouse gas (GHG) emissions or the options for smallholders to mitigate their emissions and benefit from doing so. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is coordinating research to gather the basic data on emissions that smallholder farmers and national policy makers need in order to plan sustainable futures.